The tether solution [space propulsion, electrodynamic tether]. - Johnson, L. (IEEE spectrum)
Current-carrying wire tethers are promising a cheap and reliable means and propelling spacecraft. The electrodynamic tether is a current-carrying wire that harnesses the force exerted by Earth's magnetic field. The propellant-free device could one day have several uses: to transfer working satellites to new orbits; remove defunct satellites from orbit; keep the International Space Station aloft, and even power missions to the outer planets. The technology may also be used aboard the Russians' Mir space station. An important test of the electrodynamic tether will take place in December 2000. NASA's US 7 million dollars Propulsive Small Expendable Deployer System (ProSEDS) experiment will show that an 11 kg, 5 km-long, 1.2 mm-diameter aluminum wire can rapidly remove a rocket's upper stage from orbit. The author describes basic principles of electrodynamic tether thrusters. The Earth's magnetic field exerts a force on and accelerates the wire and hence any payload attached to it. The direction of current flow through the tether, either away or towards the Earth, determines whether the magnetic force will add to or subtract from the tether's orbital energy, and therefore raise or lower its orbit